Susceptibility Modeling for Potential Fire Risk Zone in Semi-Urban Area (Journal on Geoinformatics, Nepal, 2023)
Fires inflict major losses in global forest resources as well as human lives and property. Forest fires and their tendencies have increased in recent years in Nepal that, necessity for adequate management actions. The fire risk zone is identified with the origin of the ignitions and the pattern of their occurrence, as well as by shared environmental variables that translate into the same risk potential. To reduce the detrimental impacts of fire, several strategies for preventing and combating fires have been implemented based on identified potential fire risk zone. The work is carried out in Shambhunath Municipality, Saptari. In this study, spatial modeling with integration of MCE, fuzzy and AHP is applied for susceptibility assessment for identifying the potential fire risk zone. In fire risk assessment index map shows that 21.14 percent of municipality extent land occurred in the fire risk in which the distribution of the high risk occupied 0.01 percent, medium risk, 0.49 percent, low risk 20.64 percent and remaining 79 percent land free from fire risk. The high risk of potential fire zone were identified along the east west highway surrounding to the high voltage transmission route and petrol pump location. Likewise, potential high risk of forest fire also found in the dense forest area in elevation greater than 400m.